Physical Interactions between Yeast Pichia guilliermondii and Post-Harvest Fruit Pathogen Penicillium expansum - SRI WIDYASTUTI (Bogor Agricultural University, Indonesia, 2008)
Attachment of yeast cells or bacteria on fungal hyphae have been observed in various antagonisms between microorganisms. Physical interactions between yeast Pichia guilliermondii and postharvest fruit pathogen Penicillium expansum in culture were studied in detail using light and transmission electron microscope to give better understanding on their mode of antagonism. Both organisms were co-cultured for 24-hr on potato dextrose agar. Light microscopy observations on the co-culture showed that the yeast cells attached firmly on the fungal hyphae. This attachment was inhibited by several substances such as enzymes degrading protein (protease or trypsin), a respiration inhibitor (sodium azide), an acid (hydrochloric acid) or an alkali (sodium hydroxide). Although autoclaved hyphae did not affect the attachment, but boiled enzymes and autoclaved yeast cells totally abolished the attachment. These evidences suggested that the attachment might be an active process mediated by certain protein from live yeast cells. Transmission electron micrographs on the ultrastructure of the co-culture revealed that the hyphae showed abnormalities in their structure and organelles, and a degree of obvious damage. Physical interactions observed in this study could be contributed to the mechanism of antagonism between P. guilliermondii and P. expansum. Key words: Pichia guilliermondii, Penicillium expansum, attachment, transmission electron microscope